Model of Organizational Communication in Pokdarwis Institutions Regarding Community-Based Tourism Management - Yuniati, Sri; Wirayudha, Pandu; Meisandha, Sukesih; Isra’iya, Nanda (Jurnal Ilmu Komunikasi, 2024)
Pokdarwis (the Community-Based Tourism Organizations) is a significant player in the rural management of community-based tourism. Nevertheless, obstacles remain to implement organizational communication in Pokdarwis institutions regarding the coordination of internal and external relations. The objective of this study is to identify the Pokdarwis organizational communication model in community-based tourism management. This study was carried out in Situbondo Regency, East Java. Research data was collected through observation, interviews, and a literature study. Data was analyzed using descriptive and qualitative methods with an interactive approach. The analysis of data employs descriptive and qualitative methods in conjunction with an interactive model to disclose facts in the field of Pokdarwis organizational communication. The research found an organizational communication model in Pokdarwis institutions in Situbondo Regency. Internal organizational communication consists of internal organizational activities involving Pokdarwis administrators, whereas external organizational communication entails involving the external public in administrative and legal matters and constructing cooperation networks. This research can contribute to the formulation of policies, strategies, and goals as a basis for planning, implementing, and evaluating organizational activities that are expected to influence the effectiveness of Pokdarwis' organizational communication. The proposed model provides a strategic framework for improving the performance of Pokdarwis in community-based tourism, with potential application in other rural tourism contexts.